Misallocation and manufacturing TFP in Ecuador: Formal, semi-formal and informal firms - Rafaela Bastidas; Nicolás Acosta (Journal of Economic Structures, 2019)
Resource misallocation can lower the aggregate total factor productivity (TFP). We use micro-data on manufacturing establishments from the Instituto Ecuatoriano de Estadística y Censos to quantify the differences in productivity and diagnose the efficiency in the allocation of resources between formal and informal firms in the Ecuadorian in the manufacturing sector. We use the model proposed by Hsieh and Klenow (Q J Econ 124(4):1403-1448, 2009) to find informal firms have lower physical productivity than formal firms. We also found formal firms have a restricted growth due to capital and output distortions. These results indicate the existence of an inefficient allocation of resources between firms. By reallocating resources to equalize marginal productivity in the manufacturing sector, we calculate TFP gains of 80% in 2002 and 69% in 2015.
Keywords: O47; D24; 330; Total factor productivity; Informality; Distortions; Reallocation of resources; Production factors; Ecuador